Carry trades, order flow and the forward bias puzzle - Francis Breedon; Dagfinn Rime; Paolo Vitale (Queen Mary University of London, School of Economics and Finance, 2015)
We investigate the relation between foreign exchange (FX) order flow and the forward bias. We outline a decomposition of the forward bias according to which a negative correlation between interest rate differentials and order flow creates a time-varying risk premium consistent with that bias. Using ten years of data on FX order flow we find that more than half of the forward bias is accounted for by order flow - with the rest being explained by expectational errors. We also find that carry trading increases currency-crash risk in that order flow generates negative skewness in FX returns.
Keywords: F31; G14; G15; 330; Forward premium puzzle; FX microstructure; Carry trade; Survey data